Feasibility and safety of conservative surgery for the treatment of spermatic cord leiomyosarcoma. (December 2015) - Bozzini, G.; Albersen, M.; Romero Otero, J.; Margreiter, M.; Garcia Cruz, E.; Mueller, A.; Gratzke, C.; Serefoglu, E.C.; Martinez Salamanca, J.I.; Verze, P.
Abstract: Objectives: To assess the feasibility and the safety of conservative surgery to treat spermatic cord leiomyosarcoma. Methods: Patients undergoing inguinoscrotal exploration in 10 different Urological Centers with diagnosis of leiomyosarcoma were enrolled. Preoperative evaluation included physical examination, Scrotal US, Abdominal CT and Scrotal MRI in selected cases. Patients underwent organ sparing surgery or orchiectomy in case of intraoperative FSE was positive for a local infiltration. Data collected were: age, presence of infiltration, length of the lesion, number of lesions, definitive histological outcome, pre and postoperative testosterone level. Follow up was performed with abdomen CT scan and scrotal US. Results: From January 2007 to December 2013, 23 patients (mean age: 64.7 yrs) were diagnosed with spermatic cord leiomyosarcoma. Each patients underwent scrotal US. 10 patients underwent radical orchiectomy and 13 patients underwent conservative surgery. Mean follow up was 36.5 months. 5 patients (21.7%) developed a recurrent disease, 18 patients (78.3%) had a negative follow up (mean time: 40.8 months). Statistical analysis reveals that there is a significant correlation between number of lesions, length of the lesions and recurrent disease. Conclusions: Spermatic cord leiomyosarcoma is a rare disease. Conservative surgical treatment of spermatic cord leiomyosarcoma is a feasible therapeutic option for small, single and not infiltrating lesion. Highlights: How to treat surgically spermatic cord leiomyosarcoma. European Mulcentric study, 23 patients enrolled. Spermatic cord leiomyosarcoma is a rare disease. Conservative treatment of spermatic cord leiomyosarcoma is a therapeutic option.